Le traitement de l'exemple dans le dictionnaire. - Zhu, Lichao (Cahiers du Dictionnaire, 2021)
The article propose to describe the example in the dictionary before proposing a computer-manipulable data format. Topics include considered that the objective is therefore first to show the bundle of uses of the example as a vector of meaning, which ensures the links of interdependence between the mono and polylexical units, because the latter in turn contribute to the movement reticular of meaning in a dictionary.